2023
DOI: 10.1002/ldr.4782
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls on density‐based soil organic carbon fractionations in global terrestrial ecosystems

Abstract: Categorization of soil organic carbon (SOC) into different functional subpools according to their recalcitrance and protective mechanisms helps better understand ecosystems organic carbon (OC) dynamics, and various attempts have been made to explore the suitable experimental fractionation method for such purpose. However, most previous studies neglected the influences of environmental factors on the effectiveness of varying fractionation methods. Density fractionation has shown great promise in elucidating SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…The similar MAOC pool sizes among contrasting climatic zones can be explained by the overriding controls by factors such as soil physico‐chemical properties (i.e., the contents of Fe/Al oxides; Figure 7; Figure S11d,e), because stronger ligand exchange bonding also occurs despite the increasing decomposition and desorption of mineral‐OC bonds under warmer temperature (Conant et al., 2011; Pignatello, 1999). Consequently, mineral protection in SOC persistence overrides the controls by restricted substrate accessibility and microbial activity (Gentsch et al., 2018; Lavallee et al., 2020; Qin et al., 2021; Sun et al., 2023). The MAOC pool increased under wetter climate in forests of the temperate and sub/tropical zones (Figure S11b), likely explainable by the accumulation of soil microbial necromass under more humid conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar MAOC pool sizes among contrasting climatic zones can be explained by the overriding controls by factors such as soil physico‐chemical properties (i.e., the contents of Fe/Al oxides; Figure 7; Figure S11d,e), because stronger ligand exchange bonding also occurs despite the increasing decomposition and desorption of mineral‐OC bonds under warmer temperature (Conant et al., 2011; Pignatello, 1999). Consequently, mineral protection in SOC persistence overrides the controls by restricted substrate accessibility and microbial activity (Gentsch et al., 2018; Lavallee et al., 2020; Qin et al., 2021; Sun et al., 2023). The MAOC pool increased under wetter climate in forests of the temperate and sub/tropical zones (Figure S11b), likely explainable by the accumulation of soil microbial necromass under more humid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with our first hypothesis and some prior studies (Lavallee et al., 2020; Lugato et al., 2021), here we found that the MAOC pool decreased with increasing MAT globally, especially in forests of the sub/tropical zones (Figure 6c). This response is likely caused by faster turnover of organic materials under warmer conditions that overrides the protection of SOC via the mechanism of reactive metal ions such as Fe and Al (Doetterl et al., 2015; Sun et al., 2023).…”
Section: Discussionmentioning
confidence: 99%